PENGARUH FINANCIAL ATTITUDE DAN EMOTIONAL INTELLIGENCE TERHADAP MONEY MANAGEMENT GAMERS DI PULAU JAWA - Muliadji, Adelia; Pertiwi, Dewi; Wongso, Samuel Alfred (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2023)
Money Management or financial arrangements are of course now becoming an important matter where now the situation is uncertain going forward so it is necessary to have financial arrangements at this time so that in the future there will be no shortage of funds. However, in this study the subject of this study is a community of gamers who have an interesting view of their pattern in managing their finances or how to spend them. Therefore, this study aims to look at the Financial Attitude and Emotional Intelligence of gamers in their community to see whether these variables influence how they manage their finances. Thus the researchers in their study used the Outer fit Model and Goodness Fit Outer Model Evaluation methods, as well as Hypothesis Testing. The resul, when viewed from the results of this study, there is a significant relationship between these 2 variables in their view of their financial management. They are also aware of the importance of managing their finances.